1239. Frequently Identified Infection Control Gaps in Outpatient Hemodialysis Centers. (26th November 2018) - Tyner, Kate; Nailon, Regina; Drake, Margaret; Fitzgerald, Teresa; Beach, Sue; Lyden, Elizabeth; Rupp, Mark E; Schwedhelm, Michelle; Tierney, Maureen; Ashraf, Muhammad Salman
Abstract: Background: Little is known about infection control (IC) practice gaps in outpatient hemodialysis centers (OHDC). Hence, we examined the frequency of IC gaps and the factors associated with them. Methods: The Nebraska (NE) Infection Control Assessment and Promotion Program (ICAP) in collaboration with NE Department of Health and Human Services conducted on-site visits to assess infection prevention and control programs (IPCP) in 15 OHDC between June 2016 and March 2018. The CDC Infection Prevention and Control Assessment Tool for Hemodialysis Facilities was used for IPCP evaluation. A total of 124 questions, 76 of which represented best practice recommendations (BPR) were analyzed in 10 IC domains. Gap frequencies were calculated for each BPR. Fisher's exact test was used to study the association of the identified gaps with typical patient census of the facilities and chain affiliation (CA). Results: Of the 15 OHDC, seven were large centers (typically following >50 patients) and 11 were part of national chains. Important IC gaps exist in all OHDC. A median of 64 (range 57–70) of 76 BPR were being followed by OHDC or were nonapplicable to them. The IC Program and Infrastructure domain had the highest frequency of IC gaps (Figure 1). Figure 2 describes the top 5 IC gaps. Smaller OHDC (sODHC) and those without CA performed better in a few areas. For example, a higher proportion of sODHC had work exclusion policies that encourage reporting of illness without any penalty when compared with larger OHDC (75% vs. 0, P = 0.01). Similarly, a higher proportion of sOHDC provided space and encouraged persons with symptoms of respiratory infection to sit as far away from others as possible in nonclinical areas (63% vs. 0, P < 0.05). None of the nonchain OHDC had shared computer charting terminals when compared with 64% of OHDC with CA ( P = 0.08) and a majority of nonchain OHDC provided space and encouraged persons to maintain distance with others when having respiratory symptoms as opposed to a minority of OHDC with CA (75% vs. 18%, 0.08). Conclusion: Important IC gaps exist in OHDC and require mitigation. Informing OHDC of existing IC gaps may help in BPR implementation. Larger scale studies should focus on identifying factors promoting certain BPR implementation in smaller and nonchain OHDC. Disclosures: All authors: No reported disclosures.